OPEN RECRUITMENT INFORMATION SYSTEM STUDENT EXECUTIVE BOARD USING SIMPLE ADDITIVE WEIGHTING (SAW) METHOD - Maharani, Nita; Hartono, Benedictus Shandy; Suri, Muhamad Sofwan; Dzikri, Reza Fauzan; Maulana, Septian Rizki; Yuliani, SY. (CENTRAL ASIA AND THE CAUCASUS, 2022)
Information systems make human work more accessible and more efficient. The Widayatama, University Student Executive Board (BEM) recruitment information system currently has a process the selection of members is still made manually so that the selection of members BEM takes a long time and is sometimes subjective, therefore, A decision support system is needed that can simplify the process decision making using the SAW method. The results of the literature study show that the SAW method has essential uses in assessing recruitment. This information system makes it easier for students to process BEM recruitment and register BEM management online. This information system is based on a website, using the PHP Laravel programming language, and the CSS Framework used is Bootstrap, the database used is XAMPP. With this web-based recruitment information system, it is easier for the Committee to have assessment criteria to determine whether or not members deserve to be accepted as members of the BEM.